Frontline Syria from revolution to proxy war - Phillips, David L. 1959- (I.B. Tauris, 2020)
"When the Syrian regime used sarin and other chemical weapons against dissidents in August 2013, an estimated 1729 people were killed including 400 children. President Barack Obama warned that the use of chemical weapons would constitute a "red line," but he refused to take military action. Trump's approach has been even more disengaged and lacking in clarity. Frontline Syria highlights America's failure to prevent conflict escalation in Syria. Based on interviews with US officials involved in Syria policy, as well as UN personnel, the book draws conclusions about America's role in world affairs and its potential to prevent deadly conflict. It also highlights the role of front-line states in Syria and other countries who engaged in the Syrian conflict to advance their national interests. Covering key turning points in the Syrian civil war, including the impact of recent decisions by the Trump administration, Frontline Syria critically evaluates America's global power and provides a diplomatic and military history of the conflict. Based on this analysis, the book offers policy recommendations and makes a case for America's future role addressing peace and conflict."
Keywords: Middle Eastern history / bicssc; Bürgerkrieg in Syrien; Syria / History / Civil War, 2011-; Syria / Foreign relations / United States; United States / Foreign relations / Syria